Senegal : Staff Report for the Article IV Consultation and Third Review Under the Policy Support Instrument-Press Release, and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This Article IV Consultation highlights that Senegal's macroeconomic situation is stable. Growth is expected to exceed 6 percent in 2016, while inflation remains low. The fiscal deficit has been declining steadily from 5.5 percent of GDP in 2013 and is projected to reach 4.2 percent of GDP in 2016. The current account deficit has narrowed and is projected to reach 6.5 percent of GDP in 2016, driven by lower oil prices and improved export performance. The outlook for the Senegalese economy is positive and risks are manageable, provided there is a concerted effort to continue improving economic governance.